1973
DOI: 10.1620/tjem.109.121
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Diagnostic Test for Pancreatic Disorders by Examination of Parotid Saliva

Abstract: Laboratory diagnostic tests for pancreatic diseases were carried out by examination of samples of parotid saliva in 22 patients, of whom 9 were with pancreatic disorders and 13 with disorders of other organs or systems. Trend analyses of the data thereby obtained revealed the approximate borderline values (lower for pancreatic diseases and higher for non-pancreatic disorders) for the rate of salivary secretion, its maximum bicarbonate concentration and amylase secretion to be 0.6ml per minute, 20mEq/L, and 1,0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
1

Year Published

1974
1974
2002
2002

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 10 publications
0
16
1
Order By: Relevance
“…This test was done as previously described (Kakizaki et al 1973a(Kakizaki et al , 1974.The values of this test for normal subjects were 0.204-0.707 ml/kg for the The values outsides these ranges were defined as representing pancreatic diseases.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This test was done as previously described (Kakizaki et al 1973a(Kakizaki et al , 1974.The values of this test for normal subjects were 0.204-0.707 ml/kg for the The values outsides these ranges were defined as representing pancreatic diseases.…”
Section: Methodsmentioning
confidence: 99%
“…We have recently developed a new, simple and rapid test for the diagnosis of pancreatic disorders (Kakizaki et al 1973a(Kakizaki et al , 1974. The rationale of this test was based on the findings in a number of animal and human studies that diminutions in volume, maximum bicarbonate concentration and amylase content of the parotid saliva are well correlated with the presence of pancreatitis as well as with other form of pancreatic diseases (Kakizaki et al 1971(Kakizaki et al , 1972a(Kakizaki et al , b, c, 1973bIshidate et al 1974).…”
mentioning
confidence: 99%
“…In man, Descos et al (2) observed decreased basal but normal stimulated salivary secretion in chronic pancreatitis. In contrast, Kakizaki et al (8,9) found that pilocarpine stimulated volume, maximal bicarbonate con centration and amylase content of the saliva of patients with pancreatic disorders were signifi cantly lower than in patients with nonpancreat ic disorders. Therefore, the parotid saliva test was introduced as a new diagnostic test for pancreatic diseases allegedly superior to the secretin-pancreozymin test.…”
mentioning
confidence: 90%
“…251 rats, we demonstrated that a humoral transmission mechanism participates in the development of an interactive response between the pancreas and the parotid gland (Kakizaki et al 1978). On the basis of these findings, we developed a parotid saliva test using the intramuscular injection of 1% pilocarpine hydrochloride as a screening test for the diagnosis of pancreatic disorders, and found that the test was sufficiently reliable and informative to merit an extensive clinical trial (Kakizaki et al 1973(Kakizaki et al , 1976b(Kakizaki et al , 1983. The results of our parotid saliva test have been confirmed by some other authors (Grimmel et al 1976;Nacchiero et al 1978;Noronha et al 1978;Mc Coll et a].. 1979a;Dudar and Gusak 1981;Medizova and Ivanov 1981) and disputed by some (Minaire et al 1975;Dobrilla et al 1979 ;Lankish et al 1979).…”
mentioning
confidence: 99%